Impacto del crecimiento económico sobre el ahorro: análisis de datos panel para los países de América Latina y el Caribe, periodo 1995-2020. - Yaguana Chuquirima, Roberth Fabian (2023)
Savings is the amount of income that an individual or an economy decides to retain instead of consuming and which is subsequently allocated to investment projects that promise profitability in the future. According to data and information obtained from the World Bank (2020) the average savings in Latin America and the Caribbean is below the world average, being equal to 20.23% of GDP. In this context, the objective of this research is to examine the impact of economic growth on savings in Latin America and the Caribbean during 1995-2020, through an econometric analysis of panel data, in order to propose mechanisms to boost regional savings. The data were obtained from the World Bank's World Development Indicators (2020), where 20 countries in the region were considered, excluding 13 countries due to data availability. The results indicate that economic growth has positive and significant effects on savings, but the control variable trade balance shows greater representation within the model, while the expenditure variable turned out not to be statistically significant, while gross capital formation also showed a positive and significant effect compared to savings. Thus, we conclude that economic growth is an explanatory factor when analyzing the determinants of savings. In this framework, the policy strategy to follow focuses on making efficient use of fiscal policy and trade policy simultaneously.